Density‐dependent habitat selection of spawning Chinook salmon: broad‐scale evidence and implications. (24th October 2014) - Falcy, Matthew R.; Genner, Martin
Summary An extensive body of theory suggests that density‐dependent habitat selection drives many fundamental ecological processes. The ideal free distribution and the ideal despotic distribution make contrasting predictions about the effect of total population size on relative abundances among habitats. Empirical assessment of these habitat selection models is uncommon because data must be collected over large temporal and spatial scales. I ask whether fluctuation in Chinook salmon (Oncorhynchus tshawytscha) spawner population size through time leads to different relative densities over space. Twenty‐six years of monitoring data on spawning Chinook salmon across the entire coast of Oregon, USA, were used to evaluate models that make contrasting statements about the interactions of a latent population abundance parameter with physical habitat characteristics. There is strong information‐theoretic support for models that include terms that allow the spatial variation in density to change as population size changes through time. Analysis of the best model reveals nonlinear isodars, which suggests a 'despotic' or 'preemptive' distribution of individuals across habitats, indicating that dominant or early‐arriving individuals exclude others from breeding sites. This finding has implications for genetic dynamics, population dynamics and conservation metrics of these highly valued fish. The novel application of modelling techniques used here to assess mechanisms of habitat selection from observational data can be used in the emerging field of eco‐evolutionary dynamics.